Continuity of Open Umbilical Cord Care and Risk of Neonatal Infection in a Primary Obstetric Setting: A Retrospective Cohort Study - Eyaufe, Aidevbo Otuyoma; Ibrahim, Myada; Yadav, Satya Narayan; Rysalieva, Nurgul (Journal of Health Innovation and Environmental Education, 2026)
Purpose of the study: This study aimed evaluate association between open umbilical cord care and neonatal infection within 28 days postpartum in primary midwifery facilities in Iseyin, Oyo State, Nigeria, and to identify independent biological and environmental predictors of infection risk. Methodology: A retrospective cohort design was applied to 980 term neonates delivered between January 2022 and December 2024 in six registered primary obstetric centers in Iseyin, Oyo State, Nigeria. Data were extracted from maternity registers and follow-up records. Multivariable log-binomial regression and 1:1 propensity score matching were performed using STATA version 17 to estimate adjusted relative risks (RR) with 95% confidence intervals. Main Findings: Neonatal infection occurred in 8.7% of the open cord care group and 6.5% of antiseptic group. After multivariable adjustment and propensity score matching, open cord care was not significantly associated with increased infection risk (aRR 1.15; 95% CI 0.76–1.73; p = 0.49). Low birth weight, prolonged rupture of membranes, and limited household sanitation were independent predictors, while early breastfeeding initiation was protective. Novelty/Originality of this study: This study provides context-specific effectiveness evidence on open umbilical cord care within real-world primary midwifery services in semi-urban West Africa. By integrating propensity score matching with routine service data, it bridges the gap between controlled antiseptic trials and implementation-level nursing practice, supporting risk-stratified and system-oriented neonatal infection prevention strategies.